THE IMPACT OF ETHICAL LEADERSHIP, INNOVATION ADOPTION, AND CREATIVITY ON COMPANY PERFORMANCE IN FAST FASHION INDUSTRY - Muchlison, Sonny; Sugiono, Edi; Lestari, Rahayu (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the impact of ethical leadership, innovation adoption, and creativity on company performance within Indonesia's fast-fashion industry. As the industry faces increasing scrutiny regarding sustainability and social responsibility, understanding the relationships between these organizational capabilities becomes crucial for competitive advantage. Using a quantitative methodology, this research employed saturated sampling of 87 managers from fast-fashion companies across major Indonesian cities including Jakarta, Bandung, Surabaya, and Medan. Data were analyzed using SmartPLS 4.0 through Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model demonstrated strong reliability and validity, with all constructs exceeding recommended thresholds for Cronbach's Alpha (0.832-0.873), Composite Reliability (0.883-0.911), and Average Variance Extracted (0.603-0.671). Discriminant validity was confirmed through Fornell-Larcker criterion and HTMT ratios below 0.85. The findings reveal that ethical leadership, innovation adoption, and creativity function as complementary organizational resources that collectively enhance company performance rather than operating in isolation. These results provide empirical evidence for the synergistic effects of leadership behavior, technological orientation, and creative capacity in driving organizational success. The study contributes to management literature by demonstrating the integrated nature of these capabilities and offers practical guidance for fast-fashion companies seeking sustainable competitive advantage through ethical practices, systematic innovation, and creative organizational cultures.